In their own words: 41 stories of young people's digital citizenship. Issue 4 (2nd October 2022) - Black, Rosalyn; Walsh, Lucas; Waite, Catherine; Collin, Philippa; Third, Amanda; Idriss, Sherene
ABSTRACT: Digital citizenship and cyber safety are often used interchangeably in the context of young people's internet use, depicting the young person as passive, vulnerable and in need of adult intervention to navigate an unsafe online environment and perpetuating reductive and deterministic initiatives that rarely respond to young people's own online perspectives and experiences. This discussion maps recent definitions and debates about digital citizenship and cyber safety. It draws from 41 stories of young Australians aged 12–18 to think about young people's digital citizenship within the wider context of their lived citizenship. Reflecting the deeply relational nature of young people's experiences as digital actors and how they creatively perform their citizenship online, it suggests that young people's accounts provide an opportunity to consider how citizenship is understood through digital lives and to direct educational responses that encompass emergent civic cultures emerging from young people's performance as digital citizens.